2023
DOI: 10.3390/nu15122802
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Efficacy of a Diabetic Diet Containing the Rare Sugar D-Allulose in Patients with Type 2 Diabetes Mellitus: A Prospective, Randomized, Single-Blind, Crossover Study

Kensaku Fukunaga,
Takafumi Yoshimura,
Hitomi Imachi
et al.

Abstract: High sugar consumption increases the risk of diabetes, obesity, and cardiovascular diseases. Regarding the diet of patients with diabetes, artificial sweeteners are considered a safe alternative to sugar; however, there is also a risk that artificial sweeteners exacerbate glucose metabolism. D-allulose (C-3 isomer of d-fructose), which is a rare sugar, has been reported to have antidiabetic and antiobesity effects. In this study, the efficacy of a diabetic diet containing D-allulose was investigated in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The literature reports the results of clinical studies conducted using very different doses of D-allulose, even up to 15 g per day. For example, in the paper by Fukunaga et al [45], a diabetic diet containing 8.5 g D-allulose was found to improve postprandial glucose levels in type two diabetics compared with a normal diabetic diet. A recent metanalysis by Yuma et al [46] reported a comparison between a D-allulose intake group and a control group, showing that both the 5 g and 10 g intake groups had a significantly smaller area under the curve of postprandial blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports the results of clinical studies conducted using very different doses of D-allulose, even up to 15 g per day. For example, in the paper by Fukunaga et al [45], a diabetic diet containing 8.5 g D-allulose was found to improve postprandial glucose levels in type two diabetics compared with a normal diabetic diet. A recent metanalysis by Yuma et al [46] reported a comparison between a D-allulose intake group and a control group, showing that both the 5 g and 10 g intake groups had a significantly smaller area under the curve of postprandial blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…In people with obesity, a 5-week intake of erythritol and xylitol showed no effects on glucose tolerance as well as on vascular function or abdominal fat [26]. Similarly, a diet containing allulose showed a protective effect on insulin secretion and sensitivity in diabetes patients and could reduce postprandial blood glucose concentrations also in healthy individuals [27,28].…”
Section: Randomized Controlled Trials – Evidence On Impact On Risk Fa...mentioning
confidence: 99%
“…We have reported that allulose exhibits significant physiological effects, including the normalization of body weight and fat-pad mass in obese animals under isocaloric conditions, as well as anti-hyperlipidemic, anti-hyperglycemic, and anti-diabetic properties [5][6][7]. Recent clinical studies have indicated that it can reduce postprandial blood glucose levels, can improve insulin resistance, and has potential benefits in managing obesity and type 2 diabetes (T2D) [8][9][10][11]. These effects stem from its unique metabolic properties, positioning it as a promising candidate for use as both a sugar substitute and a dietary supplement.…”
Section: Introductionmentioning
confidence: 99%